Exploring AI Chatbot Development for Gen-Z: A Study on First-Time and Experienced Voters in Pemilu - Lady Joanne Tjahyana (Jurnal Ilmu Komunikasi dan Bisnis, 2024)
Artificial intelligence (AI) chatbots have been utilized as interactive learning platforms for higher education. Gen-Z was a generation that quickly adopted the latest technology. Several Gen-Z students participated in the Pemilu (general elections in Indonesia) for the first time in 2024. Therefore, this research aimed to develop an AI chatbot to give information about Pemilu to Gen-Z voters. The researcher developed the AI chatbot with several steps: data collecting, training, evaluating, refining, and analyzing conversation data. A group of 100 Gen-Z students took part in testing the AI chatbot. The researcher discovered that it was essential to keep refining the AI chatbot by improving the datasets and putting more context in it. Next, the researcher asserted that experienced Gen-Z voters asked more questions, as they have prior knowledge of experiencing the previous elections. Most of the experienced Gen-Z voters asked advanced questions, while most of the first-time Gen-Z voters asked basic questions. Moreover, the AI chatbot was a suitable learning platform for Gen-Z as they used metacognitive strategies to experiment with their questions to get the correct information from the AI chatbot. That action automatically helped the AI chatbot to improve its performance as part of the training step.